Conversion of liquid hot water, acid and alkali pretreated industrial hemp biomasses to bioethanol. (August 2020) - Zhao, Jikai; Xu, Youjie; Wang, Weiqun; Griffin, Jason; Wang, Donghai
Graphical abstract: Highlights: Four varieties of hemp biomasses were investigated for bioethanol production. Industrial hemp biomass has a higher glucan content (40.12 to 42.71%). NaOH pretreatment enhanced delignification and boosted glucose and ethanol yields. No significant variation in ethanol yield among four hemp varieties treated by NaOH. Abstract: In this work, four varieties of hemp biomasses (Helena, SS Beta, Tygra, and Elleta Campana) pretreated with liquid hot water (LHW), H2 SO4, and NaOH were investigated for ethanol production. Physicochemical and morphological properties of the pretreated hemp biomass were characterized. LHW achieved high glucan (85–98%) and xylan (67–71%) recoveries. H2 SO4 induced significant glucan decomposition (5.9–10.6 g/L) and inhibitor formation (4.5–7.4 g/L of HMF and 2.8–4.5 g/L of furfural) in resulting slurries. Both LHW and H2 SO4 pretreatments resulted in low glucose and ethanol yields due to recondensed lignin units. NaOH pretreatment achieved high glucose and ethanol yields due to efficient lignin removal (58.6–75.3%). There was no significant variation in ethanol yield among the four hemp varieties pretreated by NaOH. H2 SO4 and NaOH pretreated biomasses showed apparent terraced-field structures and microporous protuberances. Changes in crystallinity indexes and intensities of FTIR peaks were consistent with enhanced cellulose and decreased amorphous hemicellulose.